Analisis Struktural Cerpen “Assyarru Bis-Syarri” Karya Abdul Fattah Shobri & Ali Umar - Habil Rahman Hakim; Shinta Fitria Utami (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
Literary work is the result of interpretation of the author's imagination in expressing phenomena that occur in human life. Literary works are composed of complex structures. The elements that make up the literary work relate to the others as a whole. Literary works are divided into several types, among these types there are short stories. In Arabic literature, short stories are called qissah qasirah. One of the famous Arabic short stories is "Assyarru Bis-Syarri" by Abdul Fattah Shobri and Ali Umar. The purpose of this research is to analyze the structure of the short story. From this analysis, several aspects of the short story will be known, in the form of themes, story facts, and story tools.